Promoting Pupils’ Achievement Towards Effective Cloud Computing in Mathematics Education: A Case of Using Virtual Magic Board for Teaching Surface Area - Ngozi, Ukeagbu Merry; Unamba, Eugene Chukwuemeka (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2019)
The study investigated pupil’s achievement using virtual magic board manipulative in surface area. The quasi-experimental research approach of the pre-test-post-test non-equivalent control group design was adopted. Based on the objectives, two research questions and two hypotheses guided the study. The population comprises all primary six (6) pupils in all the private schools in Owerri Municipal Council of Imo state. A sample size of one hundred and sixty-four (164) pupils participated in the study using simple random sampling technique. The instrument used for data collection is researchers made Mathematics achievement test (MAT) that was validated by two expert’s judges from mathematics education and measurement and evaluation departments. The reliability of the instrument was determined using the Pearson Product Moment correlation method which yielded a value of 0.83. The data generated were analyzed using mean, standard deviation, t-test, and ANCOVA. The hypotheses were tested at 0.05 level of significance. The results show that virtual magic board enhances primary school pupil’s achievement in a surface area and the enhancement does not significantly depend on gender. Based on the findings it is recommended that workshops and seminars should be organized for mathematics teachers on the virtual magic board.